The Gambia Education Country Status Report - World Bank (World Bank, 2012)
Many countries in Africa have placed education at the center of their social and economic development strategies. Although much has been achieved across the region, some challenges remain: millions of children are still not enrolled in primary school; girls, children from poor families, and those from rural areas are at a distinct disadvantage when it comes to schooling; and learning outcomes are weak. In addition, secondary schools are struggling to accommodate children who complete primary school, while institutions providing higher education and technical and vocational education and training often lack labor market relevance, jeopardizing future economic growth. Deeper analytical work to inform education policy is becoming increasingly important. This first Country Status Report (CSR) for The Gambia is part of an ongoing series of country specific reports being prepared by government teams technically supported by the World Bank, United Nations Educational, Scientific and Cultural Organization (UNESCO) and other development partners. These reports aim to help engage a diverse audience and to develop a shared vision for the future of the education sector, in line with the Paris declaration on aid effectiveness. The Gambia report offers not only traditional and basic indicators such as gross enrollment rates, but also analyzes the performance of the education system in terms of access, internal efficiency and learning outcomes; equity; external efficiency and its alignment with labor market needs; resource allocation and utilization; and management. It takes into account revised population data estimates and projections down to the district level that were computed by the CSR joint team and that were recently published by the Gambia bureau of statistics. The report highlights the country's significant recent progress in terms of education, and the challenges that remain. The Gambia is still among the most advanced countries in the region in terms of enrollment and completion indicators at all education levels.